Learning About Geometry and Spatial Orientation in Virtual Worlds: a VR Prototype Using Voice Commands for Preschool Education - Carvalho, Kaique; Horbylon, Camila; Vieira, Marcos; Primo, João; Felix, Juliana; Soares, Fabrizzio; Nascimento, Thamer Horbylon (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
This paper presents the development and initial validation of an interactive Virtual Reality learning platform designed for preschool-aged children. The platform enables users to explore basic concepts such as geometric shapes (circle, square, rectangle, triangle), sizes (big and small), spatial positions (left, right, center, top, bottom), and rotation through simple voice commands. Spoken instructions are recognized by the system and translated into immediate visual feedback within a playful and immersive 3D environment. A qualitative evaluation was conducted with two specialists in preschool education, focusing on the clarity of voice commands, interface navigability, and the pedagogical relevance of the activities. Findings suggest that the platform aligns with typical cognitive and motor development stages of preschoolers, supporting learning in an engaging, intuitive, and developmentally appropriate manner. Beyond its educational effectiveness, the proposal contributes to digital inclusion by offering a low-barrier, voice-based interface that can be deployed in schools situated in towns away from major urban centers, where access to advanced technologies is often limited. By integrating oral language, spatial reasoning, and immersive interaction, the platform stands out as a promising tool to enhance contemporary educational practices in early childhood settings.